STRATEGI PENGUATAN SDM BERBASIS KOMPETENSI DAN PENEMPATAN KERJA: DAMPAKNYA TERHADAP KINERJA KARYAWAN PTPN VII - Syakdiah, Halimatus; Yulanda, Delvina; Rapareni, Yussi (Ekonomika, 2025)
This study aims to analyze the effect of competence and job placement on employee performance at PTPN VII Tran Senabing Lahat. In the era of globalization and digital transformation, human resources (HR) that are competent and placed in the right position determine the effectiveness and productivity of the organization. This study uses an associative quantitative approach with a population of 69 respondents taken using the census method. Data collection was carried out through questionnaires, interviews, and observations, then analyzed using multiple linear regression with the help of SPSS version 23.0. The results showed that partially competence has a significant effect on employee performance with a significance value of 0.002. Job placement also has a significant effect partially with a significance value of 0.005. Simultaneously, competence and job placement have a significant effect on employee performance with a significance value of 0.000. The coefficient of determination (RÂ²) value of 0.388 indicates that 38.8% of variations in employee performance can be explained by competence and job placement.